Outcome of pre-term babies born in tertiary care institute - M. V., Nagaraj; P., Saravanan (International Journal of Contemporary Pediatrics, 2019)
Background: Preterm babies’ survival has improved with advances in neonatology care in this era. Even with advances in treatments, there is still morbidity and mortality among preterm. The objective of this study was to know the incidence of prematurity and complications seen in them. Methods: A cross sectional study was conducted on all preterm babies born in Sapthagiri Institute of Medical Sciences, Bangalore, over period of one year from 1st August 2017 to July 2018. Results: Out of 500 babies born, 110 babies had RDS, among 110 babies 85 cases were preterm RDS babies included in study. Majority were males 55 (64.5%) and females 30 (35.2%). The gestational age group was maximum in the 28-32weeks,the most common morbidity noted was sepsis (77.7%) and RDS (22%). Death was 9(10.5%) only 4(4.7%) needed intervention in the form of CPAP. Conclusions: The study concluded that males were commonly affected by respiratory distress syndrome, sepsis was a common cause for morbidity and mortality. Inspite of advances in neonatology sepsis continues to be a leading cause of death. Proper hand cleansing has to be emphasized and reinforced to prevent sepsis in NICU. The best possible attempts to delay preterm delivery have to be followed. One should have a high index of suspicion and low threshold to treat sepsis in preterm.